Increasing Cellulose Production from Rhizobium leguminosarum bv. viciae - Ahmed, Suaad Ali; Kazim, Alaa Raheem; Hassan, Hussam Mahmood (Al-Nahrain Journal of Science, 2017)
Bacterial cellulose (BC) is a type of biopolymer produced as primary metabolism product by many genera of bacteria such as Acetobacter, Rhizobium, Agrobacterium, Psuedomonas and Sarcina. This article aimed to study the effect of some factors on cellulose production from Rhizobium leguminosarum bv. viciae which isolated from root nodules of Vicia faba plant collected from Abu-Ghraib in Baghdad. Some environmental and nutritional factors were examined including : carbon and nitrogen sources, pH, temperature and incubation period. Results showed that maximum production of cellulose was gained by Hestrin-Schram medium (HS medium) containing 2% fructose as carbon source, 1% yeast extract as nitrogen source, as well as optimum pH, temperature, and incubation period were (5, 30°C for 7 days) respectively .Cellulose dry weight was analyzed by Fourier transform infrared spectroscopy (FTIR) technique and the results showed the presence of the functional groups of bacterial cellulose.